International Victimization Survey, 1988 and 1992 - Unknown ([Verlag nicht ermittelbar], 1990)
This survey was undertaken in 1988 and 1992 to compare crime rates for industrialized countries and to assess national crime problems by providing a crime index independent of police statistics. Fifteen countries participated in the 1988 survey, and 13 countries were included in 1992. A standardized survey instrument was employed, with Japan, Czechoslovakia, and Poland using questionnaires and sampling methods that varied slightly from the rest. The data include variables such as number of people in the household, sex of the respondent, and number of respondents in the household 16 years of age and older as well as under 16. Additional household demographic variables include employment, education, income, insurance, and city size. Crimes covered include motor vehicle theft and damage, motor bicycle theft and damage, bicycle theft and damage, housebreaking, violence, robberies, assaults, and attempts. Victim-offender relationships, crime prevention techniques, and police contact variables are also provided.